Association Between Severity of Diabetic Neuropathy and Success in Weight Loss During Hospitalization Among Japanese Patients with Type 2 Diabetes: A Retrospective Observational Study - Nakanishi S (Dove Medical Press, 2020)
Shuhei Nakanishi,1 Hidenori Hirukawa,1 Masashi Shimoda,1 Fuminori Tatsumi,1 Kenji Kohara,1 Atsushi Obata,1 Seizo Okauchi,1 Junpei Sanada,1 Yoshiro Fushimi,1 Akiko Mashiko,1 Tomoatsu Mune,1 Kohei Kaku,2 Hideaki Kaneto1 1Division of Diabetes, Metabolism and Endocrinology, Kawasaki Medical School, Okayama, Japan; 2Department of Internal Medicine, Kawasaki Medical School, Okayama, JapanCorrespondence: Shuhei Nakanishi Email n-shuhei@umin.netIntroduction: This study aimed to examine the association between severity of diabetic neuropathy and weight loss during hospitalization in overweight participants with type 2 diabetes.Patients and Methods: Participants of this study comprised 193 patients who were hospitalized for type 2 diabetes treatment. The participants were divided into two groups in the study, based on whether or not reduction of bodyweight was at least 3% during hospitalization. Using Cox models, the association between severity of neuropathy and effectiveness of weight loss under a controlled diet was analyzed. Autonomic neuropathy was assessed on patient admission by R-R interval, as measured in an electrocardiogram (CVRR), and sensory neuropathy was assessed using both 128-Hz tuning-fork vibration and Achilles tendon reflex (ATR).Results: The adjusted hazard ratio for weight loss of at least 3% for CVRR was 1.17 (95% confidence interval 1.07– 1.28, P=0.0006) and for vibration time 1.93 (1.01– 3.68, P=0.045). After dividing CVRR and vibration time into tertiles based on participant number, the adjusted hazard ratio for the high tertile of CVRR was 2.17 (1.29– 3.62, P=0.003), and for the long tertile of vibration time 1.84 (1.10– 3.08, P=0.02), compared with the low and short tertiles, respectively. No association was detected between ATR category and weight loss.Conclusion: Severity of diabetic neuropathy was found to be a determinant in weight loss under a caloric restriction regimen for patients with type 2 diabetes. The results of the study suggest that the peripheral nervous system is involved in responses to medical intervention for treatment for type 2 diabetes including bodyweight management.Keywords: diabetic neuropathy, weight loss, R-R interval as measured in an electrocardiogram, type 2 diabetes